Numerical Simulations of Nonbreaking Solitary Wave Attenuation by a Parameterized Mangrove Forest Model - Adytia, Didit; Husrin, Semeidi (International Journal of Engineering and Technology, 2019)
A numerical approach for investigating a nonlinear transformation of tsunami wave attenuation due to mangrove forest was performed.Â A dispersive nonlinear wave model so-called Optimized Variational Boussinesq Model (OVBM) is used to simulate the propagation of non-breaking solitary waves, representing tsunami waves. The wave damping by mangrove forest is modelled by adding a dissipation term due to bottom roughness in the momentum equation of the OVBM. The accuracy of the model larger than 85% is obtained by comparing results of simulation with experimental data from the hydrodynamic laboratory.Â Â